Redesigning Fertilizer Distribution Strategy of PT. Pupuk Indonesia (Persero) - Rochim, Abdul; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2017)
Abstract---This study aims to formulate the company's distribution strategy. To develop distribution strategy, internal and external corporate environmental analysis and Strategy Diamond Model are performed. The analysis begins with data collection process using interview method. Interview data is processed using qualitative research methodology Analysis result stated that PT Pupuk Indonesia's business process does not have a reliable stock procurement planning and does not integrate distribution operation activities, so currently there are fertilizer scarcity complaints in mass media. Therefore, PT Pupuk Indonesia is recommended to send the fertilizer according to the six precise principles, develop a comprehensive stock and distribution plan, implement integrated distribution control, optimize fleet usage and distribution equipment, conduct joint auction synergies, establish internal partnership between PT Pupuk Indonesia and with external parties, implement long-term service contracts, and determine optimal stockpile of fertilizers.  Keywords: Distribution, Strategy, Fertilizer, Diamond Model, Six Precise.